Dampak Wisata Religi Makam Eyang Kobul Ditinjau dari Aspek Ekonomi dan Sosial - Kunkun Kurniawan; Dadang Suganda; Ute Lies Siti Khadijah (STIEPAR YAPARI Bandung, 2021)
Tourism is a travel activity carried out by a person or group to a place to gain satisfaction, enjoyment, happiness, experience or new knowledge. Tourism activities are not only to fulfill material needs but also spiritually. The spiritual needs of a person or group come from something non-physical. One of these non-physical needs is the desire to always want to be close to people who are part of the family, figures, leaders who are honored for their services and sacrifices even though they have been physically cut off in the real world. Pilgrimage to the grave is a tradition carried out by a person or group to attribute glory to the ancestors, showing respect for a figure or leader who has contributed to visiting the glorified and sacred tomb. This study aims to determine the historical background of the Eyang Kobul gravesite and its impact on economic and social life for the surrounding community. Furthermore, the method used in this research is to use qualitative methods. The research data were collected through observation, interviews, and study of literature. The results of this study indicate that the existence of the Eyang Kobul gravesite has a positive impact on the economy and social life of the community around Jatisari Village, Kutawaringin District, Bandung Regency. The future challenge related to the development of the Pilgrimage tour of the Tomb of Eyang Kobul is how the manager with the principle of independence can realize a program of arrangement and improvement of better facilities for pilgrims.